Impact of controlled high-sucrose and high-fat diets on eosinophil recruitment and cytokine content in allergen-challenged mice. - Caroline M Percopo; Morgan McCullough; Ajinkya R Limkar; Kirk M Druey; Helene F Rosenberg (PLoS ONE)
Despite an ongoing focus on the role of diet in health and disease, we have only a limited understanding of these concepts at the cellular and molecular levels. While obesity has been clearly recognized as contributing to metabolic syndrome and the pathogenesis of adult asthma, recent evidence has linked high sugar intake alone to an increased risk of developing asthma in childhood. In this study, we examined the impact of diet in a mouse model of allergic airways inflammation with a specific focus on eosinophils. As anticipated, male C57BL/6 mice gained weight on a high-calorie, high-fat diet. However, mice also gained weight on an isocaloric high-sucrose diet. Elevated levels of leptin were detected in the serum and airways of mice maintained on the high-fat, but not the high-sucrose diets. We found that diet alone had no impact on eosinophil numbers in the airways at baseline or their recruitment in response to allergen (Alternaria alternata) challenge in either wild-type or leptin-deficient ob/ob mice. However, both bronchoalveolar lavage fluid and eosinophils isolated from lung tissue of allergen-challenged mice exhibited profound diet-dependent differences in cytokine content. Similarly, while all wild-type mice responded to allergen challenge with significant increases in methacholine-dependent total airway resistance (Rrs), airway resistance in mice maintained on the isocaloric high-sucrose (but not the high-calorie/high-fat) diet significantly exceeded that of mice maintained on the basic diet. In summary, our findings revealed that mice maintained on an isocaloric high-sucrose diet responded to allergen challenge with significant changes in both BAL and eosinophil cytokine content together with significant increases in Rrs. These results provide a model for further exploration of the unique risks associated with a high-sugar diet and its impact on allergen-associated respiratory dysfunction.